India : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Selected Issues paper for India reports that rapid growth is presenting new challenges to macroeconomic policy, although ensuring the sustainability of this growth requires broad-based fiscal and structural reforms. Higher world oil prices present risks in both the near and medium term. In the short-term, higher oil prices combined with robust domestic demand threaten to push inflation higher. Over the longer-term, permanently higher oil prices can depress growth and widen fiscal imbalances, in particular if the economy is not allowed to adjust to new price levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet